Evaluation of renal function following treatment with 5-aminosalicylic acid derivatives in patients with ulcerative colitis - KELLEHER, DERMOT P; WEIR, DONALD (John Wiley, 2002)
BACKGROUND: A number of cases of nephrotoxicity have been reported in patients with inflammatory bowel disease taking oral 5-aminosalicylic acid (5-ASA). AIM: To evaluate the effects of 9 months of therapy with mesalazine or olsalazine on renal function in patients with ulcerative colitis in remission. METHODS: Forty patients with ulcerative colitis in complete remission for 6 months were randomized to either olsalazine (n=20) or mesalazine (n=20 for nine months). Thirty-six of the 40 patients were on prior salicylate therapy. Disease activity was the measure ofclinical efficacy and was assessed by the Harvey-Bradshaw Index (HBI). Laboratory efficacy measurements included glomerular filtration rate (GFR), microalbuminuria, urinary gluthathione S-transferase (GST) and serum C-reactive protein (CRP). Safety analysis consisted of documentation of adverse events and laboratory values. RESULTS: There was no significant reduction in the GFR overall on therapy. The levels of GFR adjusted for baseline were similar in the two treatment groups after 3, 6 and 9 months. A significantly higher percentage of mesalazine-treated patients experienced drug related adverse events, all of a minor nature. The incidence of adverse events causing early withdrawal was similar in the two treatment groups. CONCLUSION: Treatment with mesalazine or olsalazine for 9 months had no significant impact on GFR.
PUBLISHED
Keywords: Clinical Medicine